Responsibly Including Survivors’ Voices in the Planning and Implementing of Educational Programmes for Healthcare Providers - Panda, Preeti; Mango, Annette; Garg, Anjali (Anti-Trafficking Review, 2021)
Survivors’ experiences and input are essential for human trafficking education for healthcare providers yet they remain under-utilised. This article describes a collaborative initiative between two paediatric physicians and a survivor of trafficking, which led to the implementation of an anti-trafficking education programme for healthcare providers. It outlines the process of establishing the collaboration and the main principles of ensuring an equitable partnership. It shares the authors’ reflections of the process and their recommendations for others seeking to establish similar initiatives.